Canadian Petroleum - Lambert, R. (Geoscience Canada, 1974)
Summary Comparison of Canada's frontier petroleum provinces with the North Sea suggests that much less oil will be found in Canada. It is concluded that the present export pattern for oil cannot be long maintained and that increased investment in petroleum exploration is essential.